2009
DOI: 10.1037/a0015815
|View full text |Cite
|
Sign up to set email alerts
|

Living with a concealable stigmatized identity: The impact of anticipated stigma, centrality, salience, and cultural stigma on psychological distress and health.

Abstract: The current research provides a framework for understanding how concealable stigmatized identities impact people's psychological well-being and health. The authors hypothesize that increased anticipated stigma, greater centrality of the stigmatized identity to the self, increased salience of the identity, and possession of a stigma that is more strongly culturally devalued all predict heightened psychological distress. In Study 1, the hypotheses were supported with a sample of 300 participants who possessed 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
554
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(614 citation statements)
references
References 98 publications
31
554
4
1
Order By: Relevance
“…This is because people who identify strongly with their social class group are more likely to be affected by its (positive or negative) social status (for conceptually similar predictions, see Elliott & Doane, 2015;McCoy & Major, 2003, p. 1007Quinn & Chaudoir, 2009). This amplification hypothesis can be contrasted with an alternative buffering hypothesis.…”
Section: The Amplification Hypothesismentioning
confidence: 82%
“…This is because people who identify strongly with their social class group are more likely to be affected by its (positive or negative) social status (for conceptually similar predictions, see Elliott & Doane, 2015;McCoy & Major, 2003, p. 1007Quinn & Chaudoir, 2009). This amplification hypothesis can be contrasted with an alternative buffering hypothesis.…”
Section: The Amplification Hypothesismentioning
confidence: 82%
“…Importance and salience can be conceived as part of the broader construct of centrality (Cameron, 2004;Milanov et al, 2014). However, they refer to separate constructs (e.g., Quinn & Chaudoir, 2009), and in the present study an exploratory factor analysis showed that they loaded on distinct factors. There are also theoretical reasons for treating these constructs separately.…”
Section: Endnotesmentioning
confidence: 70%
“…Specifically, we examined the potential moderating effects of three types of identification: the importance and salience of social class identity and the perceived similarity that people feel with other members of their social class group (e.g., Milanov et al, 2014;Quinn & Chaudoir, 2009). Importance represents the psychological centrality of a social identity in a person's selfconcept (e.g., "the group I belong to is an important reflection of who I am").…”
Section: Do Different Aspects Of Social Identification Amplify and Bumentioning
confidence: 99%
“…Conversely, disclosing stigmatized identities has several positive consequences, including greater cognitive resolution, increased relationship closeness, and decreased feelings of isolation (Quinn & Chaudoir, 2009). Further, if failure is not a stigma, the issue of revealing or concealing it will not exist.…”
Section: Public Attitude Toward Business Failurementioning
confidence: 99%